Histomorphometric evaluation of the small coronary arteries in rats exposed to industrial noise - Lousinha, Ana (2017)
Morphological changes induced by industrial noise (IN) have been experimentally observed in several organs. Histological observations of the coronary arteries showed prominent perivascular tissue and fibrosis among IN-exposed rats. The effects on the small arteries are unknown. Objective: To evaluate the histomorphometric changes induced by IN on rat heart small arteries. Methods: Twenty Wistar rats exposed to IN during a maximum period of seven months and 20 age-matched controls were studied. Hearts were transversely sectioned from ventricular apex to atria and a mid-ventricular fragment was selected for analysis. The histological images were obtained with an optical microscope using 400× magnifications. A total of 634 arterial vessels (298 IN-exposed and 336 controls) were selected. The mean lumen-to-vessel wall (L/W) and mean vessel wall-to-perivascular tissue (W/P) ratios were calculated using image J software. Results: There were no differences between exposed and control animals in their L/W ratios (p = 0.687) and time variations in this ratio were non-significant (p = 0.110). In contrast, exposed animals showed lower W/P ratios than control animals (p < 0.001), with significant time variations (p = 0.004). Conclusions: Industrial noise induced an increase in the perivascular tissue of rat small coronary arteries, with significant development of periarterial fibrosis.